2010
DOI: 10.1186/1756-0500-3-344
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobins from Aspergillus species cannot be clearly divided into two classes

Abstract: BackgroundHydrophobins are a family of small secreted proteins with a characteristic pattern of eight cysteine residues found exclusively in filamentous fungi. They have originally been divided into two classes based on their physical properties and hydropathy patterns, and are involved in the attachment of hyphae to hydrophobic structures, the formation of aerial structures and appear to be involved in pathogenicity.FindingsAnalysis of nine genome sequences from seven Aspergilli revealed fifty hydrophobins, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 28 publications
2
59
0
Order By: Relevance
“…All other hyd mutants in this study retained surface hydrophobicity, suggesting that there may be some overlapping functionality of these genes or other genes yet unidentiWed in the genome. In this regard, two recent genomic searches have identiWed a number of hydrophobin and hydrophobin-like genes in Aspergillus (Jensen et al 2010) and Trichoderma species (Seidl-Seiboth et al 2011), of which many cannot easily be categorized into class I and II types, and they form distinct clades separate from known fungal sequences with as yet unknown functions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…All other hyd mutants in this study retained surface hydrophobicity, suggesting that there may be some overlapping functionality of these genes or other genes yet unidentiWed in the genome. In this regard, two recent genomic searches have identiWed a number of hydrophobin and hydrophobin-like genes in Aspergillus (Jensen et al 2010) and Trichoderma species (Seidl-Seiboth et al 2011), of which many cannot easily be categorized into class I and II types, and they form distinct clades separate from known fungal sequences with as yet unknown functions.…”
Section: Discussionmentioning
confidence: 98%
“…Hydrophobins have typically been divided into two major classes (I and II) based on their hydropathy patterns and solubility characteristics (Wösten 2001), although more recent studies indicate that there may be other classes of fungal hydrophobin and hydrophobin-like genes (Jensen et al 2010;Seidl-Seiboth et al 2011). Class I members share physiological similarity in that they form aggregates that are highly insoluble in aqueous solution, whereas class II members form aggregates that dissolve more easily (Linder et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These amphiphilic properties have consequently raised considerable industrial interest in their application for the modification of surfaces and biopolymers (39)(40)(41)(42). However, the diversity of HFBs has thus far not been taken into account: based on their solubility in solvents, hydropathy profiles and spacing between the conserved cysteines hydrophobins are traditionally grouped into class I and class II, respectively (15,16,36,43), although it has recently been shown that this classification is more complex (32,44), and there may instead be a continuum of species-specific classes. Askolin et al (45) have shown that the properties of the class II hydrophobins HFB1 and HFB2 of T. reesei clearly differ from those reported for class I hydrophobins by forming less-stable membranes at a hydrophilichydrophobic interface and by not showing a change in secondary structure and ultrastructure at the water-air interface.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analyses indicated that all except RodDp and RodEp belong to class I; RodDp, RodEp and RodGp are of intermediate forms [6]. Only RodAp is isolated and well studied, whereas the roles of the other hydrophobins (RodBp to RodGp) in A. fumigatus are unknown and thus currently a focus of our laboratory.…”
Section: Introductionmentioning
confidence: 98%